Unintentional weight loss as presenting form of Whipple's disease. Role of PET-CT scanning and review of the literature. - Emilio Páez Guillán; Alba García Villafranca; Héctor Lazaré Iglesias; José Antonio Díaz Peromingo (Sociedade Galega de Medicina Interna, 2020)
Whipple's disease (W.D.) is a multisystemic chronic infectious disorder very rare with polymorphic clinical presentation. Diagnosis can be difficult, especially when early presentation is not the classic form. We report a case presented as isolated weight loss and review the literature focusing on the role of PET-CT scanning as a diagnostic tool.